PSXII-6 Variation in Immune Pathway Genes Associated with Tannins-containing Diets in Meat Goats: A Pilot Study. (7th December 2018) - Min, B; Mienaltowski, M; Abrahamsen, F; Wang, H; Terrill, T; Gurung, N
Abstract: The objective of this study was to determine whether the condensed tannin (CT)-containing sericea lespedeza pellet (SLP; 13.6% CT), ground pine bark (PB; 16.3% CT), or its combination (SLP+PB) would have any effects on candidate immune pathway genes approach in meat goats. 24 Kiko-crossbreed intact goats were randomly assigned to one of the 4 treats. (n = 6/treat.): 1) 30% bermudagrass hay and 70% grain mix, 2) 30% PB and 70% grain mix, 3) 30% SLP and 70% grain mix, and 4) 15% PB, 15% SLP, and 70% grain mix. All goats were slaughtered at the end of the study (d 42) and liver samples were collected and frozen at −80°C. Total RNA was extracted using QIAGEN according to manufacturer's instructions. Data were processed by the Kal's Z test. For identified immune-related pathways, genes were selected including T and B cells receptor, Zinc finger domain, Jak-STAT signaling pathway, and other candidate genes in single nucleotide polymorphism (SNP) loci. Feeding both CT-containing diets has no effect on PIK3R3, CSRNB2, CSF2RB, CLEC1A, GPR84, IL10, IL20, TNF, ITGA5, GLI1, and STAT5B genes). However, feeding the PB diet affected both negative (down regulated) responses, including PIK3CD (-14.9), PTPN6 (-7.6), IL6R (-15.1), PTPN6 (-7.6), and STAT3 (-22.6), or positive expression (up regulated) of FGD6 (17.1), PTPRB (17.7), ZDHHC17 (28.2), ZBTB39 (15.6), NAV 3 (10.4), and STAT2 (22.8). Goats fed the SLP diet affected both negative responses, including PIK3CD (-6.8), PTPN6 (-7.8), NAV3 (-5.5), PTPN6 (-7.8), STAT3 (-11.9), or positively impacted IL6R (10.8) and STAT2 (2.2) compared to control. Feeding PB and SLP mixed diets also showed intermediate responses in goat gene expression. Data suggested that CT-containing diets strongly affected on both Zn finger domains and SNP genes with more positively responses with PB diets that may more resistant to parasites infection in grazing goats.